Methods and algorithms of development of a CAD system to design automated process control systems in the transport sector - Sachkov, D I; Dimov, A V; Upyr, R U (IOP conference series. Materials Science and Engineering, 2020)
The article considers questions of creation of an intelligent CAD (Computer-Aided Design) system to design APCS (Automated Process Control System) in the transport sector. The CAD system should represent a graphic 2D engine adapted for the solution of problems of design of APCS, surrounded with an information support cloud in the form of a set of relational databases of the engineering information necessary for effective and error-free work of the APCS designers. Programs of processing information that appears on drawings, schemes and tables of the APCS projects on the basis of the algorithms adopted in this subject domain should become an essential part of information support. A CAD system should be equipped with artificial intelligence programs for processing and sorting of external information and search of mistakes in the project.